Length-Weight relationship and relative condition factor (Kn) of Tor putitora, (Hamilton 1822) of Tehri reservoir: Condition factor of Tor putitora - Thakur, Venkatesh R.; Singh, Upendra; Gupta, Monika; Jha, D. N.; Alam, Absar; Kumar, Jeetendra; Verma, Hari Om; Verma, Sushil K.; Mishra, Sandeep K.; Swain, H.S.; Das, B. K. (Journal of the Inland Fisheries Society of India, 2023)
Length-Weight relationship as well as the relative condition factor of Tor putitora of size ranging from 16.3-61.2 cm were studied from Tehri reservoir. The results revealed unique regression coefficient (b) values of 3.261, 3.471, 3.367, 3.428 and 3.274 indicating isometric growth in the month of May, June, July, September and October, respectively whereas in November and December it showed allometric growth with regression coefficient (b) of 2.526 and 2.452, respectively. The Kn values ranged from 1.043 to 1.508 with the lowest Kn in post-monsoon months, but in summer Kn value was high suggesting relatively more healthy fish stocks in summer. The observations on Kn support the opinion that the stream size or waterspread area plays a vital role in fish growth since Tehri reservoir has a larger dimension. The study also provides valuable information for the management of capture fishery resources in the Tehri reservoir.